Hypermedia literacy: an insight into English as a Foreign Language online reading processes - Hazita Azman,; Mirzaeifard, Sepideh; Zaini Amir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The advent of the Internet has generated new ways of reading for knowledge, suggesting that digital literacy is a necessity for students of this new era. Even so, there is still a dearth of knowledge in the field that can provide rich theoretical descriptions of online reading processes of English as a Foreign Language (EFL) readers in the hypertext environment. This article elucidates the perceptual learning styles and the metacognitive reading strategies of English as a Foreign Language students in hypertext reading environment. Their perceived preferred practices were elicited through a questionnaire and interviews, while actual observed online behaviours were recorded with Camtasia Studio 7. Based on these data sources, patterns of reading hypermedia texts on an online reading platform were identified and compared using NVivo 9. The findings indicated that the students’ perceived as well as their preferred learning styles and metacognitive reading strategies were mostly not performed or applied by them when they were engaged in the actual hypermedia reading environment. These differences in behaviours were contributed to the reading tasks and hypermedia tools made available by the platform facilitating their reading processes. Most significantly, the study revealed that the types of hypermedia tool available enabled them to modify their previously preferred practices for other ways of reading and comprehending the hypermedia texts. Moreover, the findings have also implied that students reading hypermedia texts online can develop different choices of sensory pathways unique to digital literacy environments. Thus the findings are significant as they contribute towards the currently limited knowledge about electronic literacy and online reading processes.